Learning through blog writing: embracing the technology - Abd Rahim, Normaliza (Penerbit Universiti Malaysia Terengganu, 2014)
Learning through Blog Writing: Embracing the Technology is the first text to stress the importance of understanding and celebrating difference as a means to becoming a more effective way of using the technology in teaching and learning. This text targets both mainstream language students and non-traditional students who range widely in age, ethnicity, race, religion, social roles and socio-economy status. The text describes basic theory in learning through blog writing, non-technical terms and offers students and educators an abundance of opportunities to analyze, understand, practice, and apply skills to real-life situations.